2002
DOI: 10.1039/b205946k
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted-2,4-endo-dimethyl-8-oxabicyclo[3.2.1]octan-3-ones as catalysts for the asymmetric epoxidation of some alkenes with Oxone®

Abstract: A range of 2-substituted-2,4-dimethyl-8-oxabicyclo[3.2.1]octan-3-ones 13-18 are available in four steps and in states of high optical purity. The fluoroketone 18 was shown to be a catalyst for the asymmetric epoxidation of stilbene, (E )-methylstilbene, phenylstilbene and chalcone (59-68% ee at 24-67% conversion) using Oxone ® as the primary oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Armstrong et al have made important contributions to the progress of this field, particularly, they rightly extolled the virtues of α-fluoro- N -ethoxycarbonyltropinone 96 as an efficient and readily recycled catalyst for the epoxidation of alkenes with Oxone (83% ee) . To improve the enantioselectivity further and to clarify the factors responsible for the asymmetric induction, many attempts to prepare bicyclo[3,2,1]octanone derivatives 95 and 97 with alternative α-substitution have been carried out. , Moreover, α-fluoroketone 98 displayed a much better ability to catalyze the asymmetric epoxidation of trans -stilbene with Oxone, for which enantiomerically enriched ketone 98 with 80% ee gave rise to stilbene epoxide with 74% ee. ,
…”
Section: 51 Simple Chiral Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Armstrong et al have made important contributions to the progress of this field, particularly, they rightly extolled the virtues of α-fluoro- N -ethoxycarbonyltropinone 96 as an efficient and readily recycled catalyst for the epoxidation of alkenes with Oxone (83% ee) . To improve the enantioselectivity further and to clarify the factors responsible for the asymmetric induction, many attempts to prepare bicyclo[3,2,1]octanone derivatives 95 and 97 with alternative α-substitution have been carried out. , Moreover, α-fluoroketone 98 displayed a much better ability to catalyze the asymmetric epoxidation of trans -stilbene with Oxone, for which enantiomerically enriched ketone 98 with 80% ee gave rise to stilbene epoxide with 74% ee. ,
…”
Section: 51 Simple Chiral Ketonesmentioning
confidence: 99%
“…239,[286][287][288][289][290][291][292][293][294][295] Moreover, R-fluoroketone 98 displayed a much better ability to catalyze the asymmetric epoxidation of trans-stilbene with Oxone, for which enantiomerically enriched ketone 98 with 80% ee gave rise to stilbene epoxide with 74% ee. 305,306…”
Section: Simple Chiral Ketonesmentioning
confidence: 99%
“…A significant activating effect by a-fluorine substitution has been observed [2][3][4][5] and then extensively studied [6][7][8][9][10][11][12][13][14][15]. We have recently shown that, during epoxidation of methyl p-methoxycinnamate (Scheme 1), enantiopure tri-substituted cyclohexanones 1-3 were more efficient, leading to higher ee% and higher yields, when the halogen was axial (1a-3a) than when the halogen was equatorial (1e-3e) [7].…”
Section: Introductionmentioning
confidence: 98%
“…Targeted measurements have been collected to avoid decomposition reactions, and accident causes have become increasingly important. Buser , et al studied synthesizing and applying epoxiconazole with organic and inorganic peroxy acid, chlorohydrin, alkyl hydrogen peroxide, hydrogen peroxide, molecular oxygen, and other as oxidants to epoxidate triazolene into epoxiconazole. However, no research from around the world has yet to report on the thermal stabilities for said substances.…”
Section: Introductionmentioning
confidence: 99%